Analisis Komponen Fisik Terhadap Kemampuan Shooting Pada Permainan Sepakbola Siswa MAN 2 Kota Makassar - Herman Herman; Achmad Karim (Universitas Pendidikan Mandalika, 2021)
This research aimed to find out: (1) the correlation between leg eye coordinationAnd shooting ability in soccer games; (2) the correlation between leg muscle strength and shooting ability in soccer games; (3) the correlation between leg power explosion and shooting ability in soccer games; (4) the correlation betweenleg eye, leg muscle strength and leg power explosion on shooting ability in soccerfor the students of physical education department of MAN 2 Kota Makassar. Thetotal sample of the research was 30 students using simple random sampling technique. Technique of data analysis was descriptive correlation, regressive analysis on the significant level was α= 0,05 using SPSS version 21. The result of the research indicated that: (1) There is a significant correlation between leg eye coordination and shooting ability in soccer games, with a value of r= 0.751 (ρ < = 0.05); (2) There is a significant correlation between leg muscle strength and shooting ability in soccer games, with a value of r =0.657 (ρ < = 0.05); (3) There is a significant correlation between leg power explosion and shooting ability in soccer games, with a value of r= 0.620(ρ < = 0.05); (4) There is a significant correlation simultneously between leg eye, leg muscle strength and leg power explosion on shooting ability insoccer for the students of physical education department of MAN 2 Kota Makassar, with the determinant coefficient (R2) = 0.679 or 67.9 %